Genetic association signal near NTN4 in Tourette syndrome. Issue 2 (21st July 2014) - Paschou, Peristera; Yu, Dongmei; Gerber, Gloria; Evans, Patrick; Tsetsos, Fotis; Davis, Lea K.; Karagiannidis, Iordanis; Chaponis, Jonathan; Gamazon, Eric; Mueller‐Vahl, Kirsten; Stuhrmann, Manfred; Schloegelhofer, Monika; et al.
<x xml:space="preserve">Abstract</x> Tourette syndrome (TS) is a neurodevelopmental disorder with a complex genetic etiology. Through an international collaboration, we genotyped 42 single nucleotide polymorphisms (p < 10−3) from the recent TS genomewide association study (GWAS) in 609 independent cases and 610 ancestry‐matched controls. Only rs2060546 on chromosome 12q22 (p = 3.3 × 10−4) remained significant after Bonferroni correction. Meta‐analysis with the original GWAS yielded the strongest association to date (p = 5.8 × 10−7). Although its functional significance is unclear, rs2060546 lies closest to NTN4, an axon guidance molecule expressed in developing striatum. Risk score analysis significantly predicted case–control status (p = 0.042), suggesting that many of these variants are true TS risk alleles. Ann Neurol 2014;76:310–315